Polyimides for semiconductor applications - Satou, H.; Suzuki, H.; Makino, D.
A wide variety of polymeric materials are used in the manufacture of semiconductor devices. Examples include polymers for use as photoresists in microfabrication and epoxy moulding compounds used in electronic packaging.
Keywords: PASSIVATION FILM; BREAKDOWN VOLTAGE; SODIUM LAURYL SULFATE; POLYIMIDE FILM; POLYAMIC ACID